2019
DOI: 10.15517/ijds.v0i0.36150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Alternatives for the Use of Compactable and Flowable Bulk-Fill Composites: A Step-by-Step Case Report

Abstract: The use of Bulk-Fill composite resins to perform posterior restorations has been massified in recent years in the different clinical disciplines of Dentistry.  This may be due mainly to the simplicity in the application technique of this material as it requires its insertion into the cavity preparation in 4-5mm of composite resin thickness, achieving a considerable reduction of clinical working time. Given the existence of different viscosities of this type of composite resins, certain difficulties have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Cuentan con partículas de un tamaño entre 10 y 50 μm debido a esta característica poseen una resistencia a las fracturas junto con una mayor carga de relleno aumentando también su durabilidad sin embargo existen ciertas desventajas como la dificultad para pulirlas lo cual nos va a generar una superficie más rugosa y molesta para el paciente así como una mayor acumulación de placa, además posee una menor radiopacidad volviéndola radiolúcida [26]. Estas resinas tienen la presencia de quarzo y vidrio de estroncio en su componente inorgánico [27].…”
Section: Resinas De Macrorellenounclassified
“…Cuentan con partículas de un tamaño entre 10 y 50 μm debido a esta característica poseen una resistencia a las fracturas junto con una mayor carga de relleno aumentando también su durabilidad sin embargo existen ciertas desventajas como la dificultad para pulirlas lo cual nos va a generar una superficie más rugosa y molesta para el paciente así como una mayor acumulación de placa, además posee una menor radiopacidad volviéndola radiolúcida [26]. Estas resinas tienen la presencia de quarzo y vidrio de estroncio en su componente inorgánico [27].…”
Section: Resinas De Macrorellenounclassified
“…A comparison between compactable and flowable bulk-fill composite resins revealed that compactable resins exhibit superior physical-mechanical properties, including conversion value, elastic modulus, flexural strength, and surface hardness 24 . The distinct advantages of these resins have propelled their widespread global use, allowing for increased thickness in restorations.…”
Section: Introductionmentioning
confidence: 99%
“…The distinct advantages of these resins have propelled their widespread global use, allowing for increased thickness in restorations. This capacity is attributed to the dynamic interaction between photoinitiators and the high transparency inherent in these materials 24 . Moreover, in vitro studies examining the compressive strength of conventional and bulk-fill resins have consistently underscored the enhanced strength of bulk-fill composite resin 25 .…”
Section: Introductionmentioning
confidence: 99%